Pembrolizumab-axitinib versus nivolumab-cabozantinib as first-line therapy in patients with metastatic renal cell carcinoma: a retrospective real-world comparison (ARON-1) - Matteo Santoni; Giandomenico Roviello; Enrique Grande; Ugo De Giorgi; Ondrej Fiala; Emmanuel Seront; Javier Molina-Cerrillo; Renate Pichler; Zin W. Myint; Jakub Kucharz; Ravindran Kanesvaran; Thomas Büttner; et al. (Cancer Immunology, Immunotherapy)
Abstract Background The optimal first-line therapy for metastatic renal cell carcinoma (mRCC) remains uncertain, despite recent advancements in immune-based combinations. This retrospective study compares the effectiveness of pembrolizumab plus axitinib (PA) and nivolumab plus cabozantinib (NC) as first-line treatments for mRCC in a real-world setting. Methods Patient data were collected from 55 centers across 16 countries, encompassing individuals diagnosed with mRCC receiving first-line treatment with PA or NC between January 2016 and October 2023. Clinical and tumor features and treatment responses were recorded. The primary endpoints were overall response rate (ORR), overall survival (OS), progression-free survival (PFS), and time to second progression. Statistical analyses included Kaplan–Meier survival estimates, Cox proportional hazard models, and chi-square tests. Results A total of 760 patients with a median age of 64 years (range, 29–88) were included. Of them, 607 received PA, and only 153 NC. In the overall study population, ORR was 59% for and 49% for PA. Median OS was 55.7 months and not reached (NR) for PA and NC, respectively (P = .51), while median PFS was longer with NC (27.6 months) than for PA (16.2 months, P = .003). Subgroup analysis suggested a PFS benefits for NC in male, younger patients, intermediate risk group, clear cell histology, and lung involvement, as well as ORR favored NC in good risk patients. Multivariate analysis identified first-line therapy as a significant factor associated with PFS. Conclusions In this certainly biased retrospective comparison, NC demonstrated superior ORR and longer PFS compared to PA in mRCC. These findings underscore the importance of considering individual patient characteristics and risk profiles when selecting first-line therapy for mRCC.